TEACHER QUESTIONING BEHAVIOR ON CLASSROOM INTERACTION IN TEACHING READING OF ENGLISH CLASSES - MAS’UD, AZURA PRAMESWARA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords : teacher questioning, teaching reading, classroom interaction, type of questions This research is about the types of questions used by the teacher in teaching English particularly in reading section and how the contributions of that questions to classroom interaction. There are two types of questions in teachingreading; they are text dependent questions and text independent questions. Theinteractions can be seen through the students’ responses in answering teacherquestioning.This research uses mixed method. The data sources are two eleventh  grades English classes. The both class are XI IS-2 from MAN Pasuruan and XI MIA-1 from SMAN 1 Pasuruan, which conduct the teaching reading, and two professional English teachers of both classes. The instruments that are used in data collection are video recording, classroom observation, collecting documents, and interviews. In analyzing the data, the researcher uses symbols on the classroom interaction transcriptions in dividing the questions types. Concluding and interpretation are used to analyze the result of interview.The finding shows that text independent questions encourage the students to produce 6.8 words longer compare to text dependent questions that only encourage 6.4 words in every one question that is asked by the teacher. For the question structure, wh-questions type creates 55.9% of all questions, it is  followed by yes/no question by creating 22.7% and other questions with only create 19.5%. In addition, both of the teachers acknowledge that asking questions is an important activity. Based on both of the teachers’ opinions, they have different perspective to the importance of the two types of questions.The conclusion of this study for the students who are passive, then the teacher should give more text dependent questions. In contrary, for the students who always fast in responding the teacher talk and are always confident in sayingtheir opinion, then the teacher should give more text independent questions. Some suggestion are also offered related to the finding. First, teacher has to understand the students behavior before decide on which types of questions s/he want to use often. Second, teacher has to keep using yes/no questions to encourage the weak learners to keep responding to the teacher’s questions. Third, the use of other questions, which are created as incomplete sentence and used only to confirm the statement may be decreased.